The Potential Use of Actinomycetes as Microbial Inoculants and Biopesticides in Agriculture - Silva, Guilherme da Cruz; Kitano, Isabella Takahashi; Ribeiro, Iron Amoreli de Figueiredo; Lacava, Paulo Teixeira (Frontiers in Soil Science, 2022)
The use of fertilizers and chemical pesticides promotes significant improvements in crop development, but some problems and risks associated with them limit their application. An alternative is using biological inputs based on microorganisms, increasing production while combining efficiency and sustainability. Actinomycetes are a group of bacteria belonging to the phylum Actinobacteria, recently re-named Actinobacteriota. They represent important microbial communities in the soils with increasing agricultural applications, especially in the biological control of insect-pest and plant disease and in plant growth promotion. Studies report their promising use as microbiological inoculants by exploring mechanisms to improve plant development, such as biological nitrogen fixation, phosphate solubilization, production of phytohormones, and other biocompounds. In addition, many species produce metabolic pathways that generate high-value antibiotics, extracellular enzymes and secondary metabolites other than antimicrobials, with potential in the control of phytopathogenic fungi, insects, and nematodes. These actinomycetes could be used to formulate novel bioinoculants composed of spores and/or mycelium. Considering that the research in this field is up-and-coming, with significant economic and environmental impacts in the future, this review aims to group the most relevant works that explore the biodiversity of actinomycetes, helping to develop inoculants and biodefensives for more productive and conscious agriculture.